2004
DOI: 10.1248/jhs.50.660
|View full text |Cite
|
Sign up to set email alerts
|

Disaccharide Composition of Glycosaminoglycan Chains in Growing Vascular Endothelial Cells in Culture after Exposure to Lead

Abstract: Heparan sulfate (HS) chains bind and activate fibroblast growth factor-2 (FGF-2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Nolan and Shaikh 25) suggested that the initial effect of acute cadmium administration is on the integrity and permeability of the vascular endothelium and other necrotic changes in the underlying tissue occur secondarily. We have shown that cadmium, 26,27) lead, [27][28][29] arsenite, 30) and the biologically active sulfated polysaccharide sodium spirulan [31][32][33] influence the functions, including proteoglycan metabolism, of vascular endothelial cells. Proteoglycans are involved in the regulation of vascular endothelial cell functions; however, excluding a few exceptions such as the inhibition of vascular endothelial repair by lead, the toxicity or biological activity that mediate altered proteoglycan metabolism has not been completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…Nolan and Shaikh 25) suggested that the initial effect of acute cadmium administration is on the integrity and permeability of the vascular endothelium and other necrotic changes in the underlying tissue occur secondarily. We have shown that cadmium, 26,27) lead, [27][28][29] arsenite, 30) and the biologically active sulfated polysaccharide sodium spirulan [31][32][33] influence the functions, including proteoglycan metabolism, of vascular endothelial cells. Proteoglycans are involved in the regulation of vascular endothelial cell functions; however, excluding a few exceptions such as the inhibition of vascular endothelial repair by lead, the toxicity or biological activity that mediate altered proteoglycan metabolism has not been completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that lead, a heavy metal, inhibits vascular endothelial cell proliferation by lowering the response to endogenous FGF-2 through the suppression of perlecan synthesis 6) although the length 6) and disaccharide composition of the heparan sulfate chains are not changed. 7) This suggests that zinc and lead have opposite effects on the proliferation of vascular endothelial cells because zinc intensifies the activity of endogenous FGF-2, and lead suppresses this activity; however, the mechanisms by which these metals change the FGF-2 activity is different. In particular, inhibition by lead is mediated by suppression of the perlecan synthesis whereas stimulation by zinc is induced by mechanisms other than proteoglycan synthesis.…”
Section: Firstmentioning
confidence: 99%
“…4) It was shown that lead, a toxic heavy metal, inhibits the repair of the damaged monolayers of endothelial cells by lowering the cell response to endogenous FGF-2 due to the inhibition of perlecan synthesis, the core protein of a large heparan sulfate proteoglycan. 5) However, it was suggested that lead did not change the length 6) and the microstructure 7) of heparan sulfate chains. In contrast to lead, zinc stimulates the proliferation of vascular endothelial cells; this proliferation which is dependent on endogenous FGF-2, 8) results in repair of damaged monolayers of the cells.…”
Section: Introductionmentioning
confidence: 99%